Aberrant plumage colouration in birds from the collection of the Sarisske Museum Bardejov, Slovakia. Issue 3 (2nd October 2017) - Mikula, Peter; Čanády, Alexander; Hromada, Martin
Abstract: In this paper, we present results of the study on the aberrant plumage colouration of the bird specimens deposited in the collection of the Sarisske Museum Bardejov (SMB), Slovakia. Out of 5047 Slovak specimens stored in SMB, colour aberrations were found in 14 birds: six specimens of Passer domesticus, two specimens of Hirundo rustica, two specimens of Motacilla alba, Buteo buteo, Upupa epops, Phoenicurus phoenicurus and Pica pica (one specimen each). The most common plumage aberration was progressive greying (six cases), followed by dilution (four cases), ino (two cases), leucism and albinism (one case each).